Presidential Address: A View From the Lectern - Rea, J. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1991)
AbstractThis paper explores the relationship among teaching, research, and publications for, the author argues, a good teacher must carry out advanced historical research and >report results to a wider academic audience. This observation leads to an examination of three kinds of questions which challenge the historian as teacher: the first, questions to which the primary and secondary literature provide no answer; the second, questions to which standard works offer no adequate response but which inspire research and rethinking and thereby lead to a new understanding of the issue; and the third, questions which can be fully answered only by informed speculation. The paper then illustrates the challenge posed by each type of question by looking at important incidents in twentieth-century Canadian history: the first, why Prime Minister Borden on 1 January 1916 doubled Canada's manpower in the Great War to five hundred thousand; the second, why did the tariff disappear as an issue from elections after 1935; and the third, why did the Cabinet accept the forced resignation of J. L. Ralston as Minister of National Defence in November of 1944? The specialised knowledge required to respond to such questions necessarily enriches our overall understanding of the past.